Analisis Dampak Pemberdayaan Ekonomi pada Program DD Farm dalam Meningkatkan Pendapatan Mustahik - Muh. Ahsan Kamil; Syahriyah Semaun; Rachmat Sugeng; Ainul Fatha Isman; Abdullah Fauzan (Universitas Islam Negeri Alauddin Makassar, 2025)
There are various zakat-based economic empowerment models managed by amil zakat institutions in Indonesia, one of which is the Dompet Dhuafa Farm program. It uses a quantitative method, with data collection techniques such as interviews and documentation. The data obtained was analysed using the Wilcoxon t-test. The findings of this study are that the DD Farm program's mustahik economic empowerment model creates a livestock business by appointing mustahik as stable employees who manage on-farm and of farm processes so that they get a steady income. The results of the Wilcoxon t-test show that Mustahik's income was different before and after working in the DD Farm program. The DD Farm empowerment model has a positive impact on increasing mustahik income but is not yet perfectly adequate because some mustahiks still have incomes below the regional minimum wage.